Use of Small Architectural Forms in Greening Public Places of Historical Cities (On the Example of Khiva) - Jurat Khamroyevich Tajibaev (Genius Journals, 2022)
This article presents the results of the use of small architectural forms created with the help of plants in the organization of public spaces of historical cities, their connection with national motifs and the impact of the urban environment on environmental protection. The process of beautification of historic cities includes urban public landscapes and recreational areas, and it is advisable to organize them on the basis of the rules of "design code". In the context of the study of socio-cultural changes in historical cities from the point of view of urban planning, it is possible to study the methods of organization of recreation areas, the peculiarities of the design of open urban spaces
Keywords: Historical cities; design code; community centers; small architectural forms